Analisis Loss Learning Di SMP Insan Mandiri Pada Masa Pandemi Covid-19 - Ferlia, Wahyuni; Putra, Rizki Wahyu Yunian; MKS, Meyronita Firja; Fajar, Rahmat (Jurnal Simki Pedagogia, 2023)
Loss learning is a term used to describe learning that is not optimal in schools. The purpose of this research is to see if there is loss learning at SMP Insan Mandiri Bandar Lampung. The method used in the descriptive research with qualitative analysis of the location in this study was to take place at SMP Insan Mandiri Bandar Lampung with principals, waka and teachers as informants. The results in this study are that loss learning actually occurred before Covid-19, for example students who did not understand multiplication and other material. The emergence of Covid-19 exacerbated the emergence of loss learning at Insan Mandiri Middle School in the first year of only 10-20% but in the second year it reached 70-80% of students who experienced loss learning from various factors.